HORIZONTAL POSITIONAL ACCURACY OF GOOGLE EARTH’S IMAGERY OVER RURAL AREAS: A STUDY CASE IN TAMAULIPAS, MEXICO - PAREDES-HERNÁNDEZ, CUTBERTO URIEL; SALINAS-CASTILLO, WILVER ENRIQUE; GUEVARA-CORTINA, FRANCISCO; MARTÍNEZ-BECERRA, XICOTÉNCATL (Boletim de Ciências Geodésicas, 2013)
Due to the popularity of Google Earth (GE), users commonly assume that it is a credible and accurate source of information. Consequently, GE’s imagery is frequently used in scientific and others projects. However, Google states that data available in their geographic products are only approximations and, therefore, their accuracy is not officially documented. In this paper, the horizontal positional accuracy of GE’s imagery is assessed by means of comparing coordinates extracted from a rural cadastral database against coordinates extracted from well-defined and inferred check points in GE’s imagery. The results suggest that if a large number of well-defined points are extracted from areas of high resolution imagery, GE’s imagery over rural areas meets the horizontal accuracy requirements of the ASPRS for the production of “Class 1” 1:20,000 maps. Nonetheless, the results also show that georegistration and large horizontal errors occur in GE’s imagery. Consequently, despite its overall horizontal positional accuracy, coordinates extracted from GE’s imagery should be used with caution.